2017
DOI: 10.1371/journal.pone.0176307
|View full text |Cite
|
Sign up to set email alerts
|

The burden of trisomy 21 disrupts the proteostasis network in Down syndrome

Abstract: Down syndrome (DS) is a genetic disorder caused by trisomy of chromosome 21. Abnormalities in chromosome number have the potential to lead to disruption of the proteostasis network (PN) and accumulation of misfolded proteins. DS individuals suffer from several comorbidities, and we hypothesized that disruption of proteostasis could contribute to the observed pathology and decreased cell viability in DS. Our results confirm the presence of a disrupted PN in DS, as several of its elements, including the unfolded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 102 publications
10
42
0
Order By: Relevance
“…These findings inspired our interest in investigating possible PN dysfunction and the presence of a dysregulated protein quality control system in DS. Recently, our laboratory has reported a dysfunctional PN in DS models with increased presence of ER stress, limited chaperone expression after heat stress and increased sensitivity to proteotoxic compounds (8). Our findings here build upon this previous research and focus on further characterizing the possible pathogenic role of PN disruption via the study of the autophagic process in DS models.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These findings inspired our interest in investigating possible PN dysfunction and the presence of a dysregulated protein quality control system in DS. Recently, our laboratory has reported a dysfunctional PN in DS models with increased presence of ER stress, limited chaperone expression after heat stress and increased sensitivity to proteotoxic compounds (8). Our findings here build upon this previous research and focus on further characterizing the possible pathogenic role of PN disruption via the study of the autophagic process in DS models.…”
Section: Discussionsupporting
confidence: 72%
“…Previous research from our laboratory and others has revealed the presence of a dysfunctional proteostasis network (PN) in DS cell models, characterized by several markers of disrupted proteostasis (8)(9)(10)(11)(12). More specifically, DS cells exhibit basal endoplasmic reticulum (ER) stress, increased abundance of polyubiquitinated proteins and decreased proteasomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, these cells were hypersensitive to heat or ER stressors. Unlike control euploid cells, in which expression of heat shock proteins (HSP) increased in response to heat shock stress, HSP90 and HSP70 expression showed no changes under a moderate heat shock in aneuploid cells (Aivazidis et al, 2017). This is likely due to a pre-existing stress state in the aneuploid cells that compromises the induction of HSP expression.…”
Section: Aneuploidy-associated Stressmentioning
confidence: 92%
“…Disruption of the proteostasis network and accumulation of misfolded proteins occur as a result of an abnormality in the number of chromosome 21 [12]. Errors in protein homeostasis could contribute to the observed pathology and decreased cell viability in children with Down syndrome [13].…”
mentioning
confidence: 99%